ИНКЛЮЗИВНОЕ ОБРАЗОВАНИЕ В НАЧАЛЬНОЙ ШКОЛЕ:ОПЫТ, ПРОБЛЕМЫ, ПЕРСПЕКТИВЫ. - Утрясова Татьяна Анатольевна (TADQIQOTLAR, 2026)
The term "inclusive education" is heard from various people: teachers, parents, deputies, public figures, scientists, and heads of educational organizations. There is a gradual change in attitudes towards people with mental and physical disabilities. Today, the strategic direction is to include children with special needs in the general flow, which is known as inclusion. Based on the provisions of the UN Declarations, Conventions, and Recommendations on Human Rights, these children include: children with health issues (psychophysical disabilities, HIV and AIDS-infected children, and others); The main goal of inclusive education is to ensure that children with disabilities receive education in their local communities in accordance with their cognitive abilities and needs, to promote their social adaptation and integration into society, and to enhance the role of families in the upbringing and development of their children. Inclusive (French inclusif – including, from Latin. include – I conclude, I include) or inclusive education is a term used to describe the process of teaching children with special needs in general education (mass) schools. Inclusive education is based on an ideology that excludes any discrimination against children, ensures equal treatment for all people, but creates special conditions for children with disabilities. The organization of education for children with developmental disabilities is a long- term strategy that requires patience, consistency, continuity, and a comprehensive approach to its implementation, which is why the issues of inclusive education remain relevant.